2010
DOI: 10.2174/157339910790442655
|View full text |Cite
|
Sign up to set email alerts
|

Zinc, Alpha Cells and Glucagon Secretion

Abstract: Zinc concentrates in islet cells and is related to insulin secretion. Islet cells act as a unit within islets and hormone secretion in the islets is profoundly influenced by paracrine and autocrine regulation. Zinc has been recognised as a candidate paracrine inhibitor of glucagon secretion in alpha-cells. Further zinc fluxes may contribute to regulation of cell mass, Zn2+ may be cytotoxic and Zn2+ depletion by itself can cause cell death induced by oxidative stress. Recently, both free zinc ions and a number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…ZnT8 appears largely dispensable for α-cell function because α-cell-specific ZnT8 knockout mice show no evident abnormalities in plasma glucagon and glucose homeostasis (Wijesekara et al 2010). Nevertheless, since tiny amounts of Zn 2+ can still be present in the cells independently of ZnT8 (Egefjord et al 2010;Gyulkhandanyan et al 2008), these experiments do not exclude the remote possibility that Zn 2+ can affect somehow glucagon secretion.…”
Section: Znmentioning
confidence: 93%
See 1 more Smart Citation
“…ZnT8 appears largely dispensable for α-cell function because α-cell-specific ZnT8 knockout mice show no evident abnormalities in plasma glucagon and glucose homeostasis (Wijesekara et al 2010). Nevertheless, since tiny amounts of Zn 2+ can still be present in the cells independently of ZnT8 (Egefjord et al 2010;Gyulkhandanyan et al 2008), these experiments do not exclude the remote possibility that Zn 2+ can affect somehow glucagon secretion.…”
Section: Znmentioning
confidence: 93%
“…High extracellular local concentrations of zinc (μM) are therefore anticipated within the islet (Huang et al 1995). It has been suggested that Zn 2+ released from stimulated β-cells inhibits glucagon release (Ishihara et al 2003) and might therefore be responsible for the inhibitory effect of glucose (Egefjord et al 2010;Hardy et al 2011). A "switch-off" hypothesis involving Zn 2+ instead of insulin has also been suggested (Zhou et al 2007;Robertson et al 2011).…”
Section: Znmentioning
confidence: 99%
“…C-peptide and amylin form 1:1 heterodimers with insulin, thus removing insulin oligomers and suppressing aggregation (36). Zinc ions localize to the granules of α-cells, where a zinc-specific stain detects them at the membrane (37). Their secretion is thought to have an autocrine effect on α-cells as well (30).…”
Section: Zinc In Pancreatic Islet Physiologymentioning
confidence: 99%
“…Additionally, Egefjord et al [40] investigated that zinc regulate glucagon secretion from pancreatic acells. As a result, glucagonstimulated hepatic pathways (i.e., glycogenesis and gluconeogenesis) would be suppressed in the fasting state [41] contributing to a reduction of fasted glucose levels.…”
Section: F CLmentioning
confidence: 99%